Overtourism and tourismphobia: A systematic literature review - Veríssimo, Medéia (2021)
This paper aims at examining how overtourism and tourismphobia are being approached as emergent research topics in current tourism literature. It conducts an analysis of 154 documents, indexed in the Web of Science (WoS) Core Collection and Scopus databases. The study follows a quantitative and qualitative approach, with the support of VOSviewer and HistCite softwares for a descriptive content analysis. The analysis focuses on highlighting important aspects in terms of the most frequent publication sources (authors and journals); co-citation, as well as dimensions and research streams; methodologies used; results obtained; and implications for future research. The literature review unveiled that the concepts of overtourism and tourismphobia are usually related to destinations' development, negative impacts, and tourism policies and regulation. Results show that, although tourism excesses and conflicts have been studied for long, ‘overtourism' and ‘tourismphobia' have become usual terms, mainly within the past three years. Even though the adoption of the terms can be considered by some as a ‘trend', the in-depth analysis of the topics shed light on how ‘old' concepts can evolve to adapt to contemporary tourism issues. Further studies are needed in tracking the evolution of these topics and their implications on the future of tourism.